Simulated client study on the dispensing practices for narcotic and psychotropic medications in community drug outlets in Ethiopia - Tirsit Ketsela Zeleke; Minichil Chanie Worku; Bantayehu Addis Tegegne; Fasil Bayafers Tamene; Gebremariam Wulie Geremew; Samuel Agegnew Wondm; Aschalew Mulatu Tefera; Ayelign Eshete Fitgu; Tekletsadik Tekleslassie Alemayehu; Muluken Adela Alemu; Rahel Belete Abebe; Kale Gubae; et al. (Drugs in Context)
Background: Dispensing prescription-only medications without a valid prescription poses significant public health risks, including inappropriate drug use, adverse drug reactions and medication dependence. Narcotics and psychotropic drugs are particularly vulnerable to misuse. Despite this, limited data exist on the dispensing practices of these medications at community drug retail outlets in Ethiopia. This study aimed to assess the extent and factors of non-prescription dispensing of narcotic and psychotropic medications at community drug retail outlets in Ethiopia.